2011
DOI: 10.1007/s10750-011-0684-6
|View full text |Cite
|
Sign up to set email alerts
|

Chytrid infection reduces thoracic beat and heart rate of Daphnia pulicaria

Abstract: Zooplankters are hosts to numerous endoand ectoparasites, some of which have dramatic impacts on their hosts. Epizootics on zooplankton are probably more widespread in lake systems than it is currently known, and few studies have explored the direct and indirect importance of parasitism in aquatic food webs. In addition, our understanding of the sublethal effects of parasitic infections on host organisms and populations is limited. We used a novel electro-chemical based technique to measure in the outflow of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Thoracic limbs play an important role in the process of ventilation and their movement frequency is a common physiological marker of D. magna metabolic activity and this parameter may be altered by various environmental stressors (Pirow et al, 1999;Penalva-Arana et al, 2011). The current study indicated that H 2 O 2 alone reduced thoracic limb movement probably by oxidation of cell membrane proteins and lipids of nerve and muscle cells resulting in the depressed neuromotor activity (Keller and Mattson, 1998;Aoi et al, 2004).…”
Section: Heart Rate and Thoracic Limb Movementmentioning
confidence: 50%
“…Thoracic limbs play an important role in the process of ventilation and their movement frequency is a common physiological marker of D. magna metabolic activity and this parameter may be altered by various environmental stressors (Pirow et al, 1999;Penalva-Arana et al, 2011). The current study indicated that H 2 O 2 alone reduced thoracic limb movement probably by oxidation of cell membrane proteins and lipids of nerve and muscle cells resulting in the depressed neuromotor activity (Keller and Mattson, 1998;Aoi et al, 2004).…”
Section: Heart Rate and Thoracic Limb Movementmentioning
confidence: 50%
“…It should be noted that no immobilization of Daphnia magna treated by TOB-Eu 3+ was observed, and the TOB-Eu 3+ treatment did not induce a significant change on the heart rate of Daphnia magna (~200 beats per minute) during the incubation 37 , which suggests that the probe is biocompatible and low-toxic for in vivo imaging of vitamin C in living bodies.…”
Section: Resultsmentioning
confidence: 91%
“…Thoracic limb movement is a common physiological marker of Daphnia magna metabolic activity and its rate may be altered by various environmental stressors (Pirow et al, 1999a ; Penalva-Arana et al, 2011 ). Heat stress of Daphnia magna results in initial stimulation of thoracic limb activity and its subsequent decrease at sublethal temperature (Paul et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%